Antioxidant Potential of Lamiaceae Herbs from Botanical Garden of Slovak University of Agriculture in Nitra - Mňahončaková, Erika; Vergun, Olena; Svydenko, Liudmyla; Horčinová Sedlačková, Vladimira; Hrúzová, Michaela; Brindza, Jan; Ivanišova, Eva (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
Polyphenol compounds are the secondary metabolites of plant origin that are widely distributed. They exhibit a wide spectrum of biological activities, among which is antioxidant activity. Investigation of polyphenol content and their antioxidant activity of aromatic herbs was the main goal of this study. Plant material of this study was Hyssopus officinalis L., Lavandula angustifolia Mill., Nepeta kokanica (Regel) Kuntze, Rosmarinus officinalis L., Salvia officinalis L., Thymus serpyllum L., and Th. vulgaris L. (Lamiaceae Lindl.) harvested from the collection of the Botanical Garden of Slovak University in Nitra at the period of flowering. It was determined the total content of polyphenols (gallic acid equivalent (GAE)), flavonoids (quercetin equivalent (QE)), phenolic acids (caffeic acid equivalent (CAE)), antioxidant activity (Trolox equivalent (TE)) and reducing power (TE) of extracts. All measurements carried out on the spectrophotometer Jenway (6405 UV/Vis, England). In our study total content of polyphenols among investigated plant extracts was from 39.43 to 62.87 mg GAE.g-1 of DW (dry weight); the content of flavonoids was from 20.80 to 36.80 mg QE.g-1 of DW; content of phenolic acids was from 4.91 to 24.30 mg CAE.g-1 of DW; antioxidant activity by DPPH-method was from 7.78 to 8.50 mg TE.g-1 of DW; antioxidant activity by phosphomolybdenum method was from 122.92 to 225.36 mg TE.g-1 of DW. Thus, we found that among investigated plants S. officinalis extracts had the highest amount of polyphenol compounds, phenolic acids, and flavonoids. Antioxidant activity and reducing power was maximal for plants of H. officinalis. All investigated plants are a potential source of natural antioxidants and have potential as therapeutic agents.